Tourism and online communication: interactivity and social web in official destination websites (Communication & Society, 2015)
Websites are an important communication tool in destination branding. This study analyses the relational nature of 87 official destination websites (ODWs) according to two parameters: interactivity, whose link to ODWs has been highlighted in several studies; and, the presence of the social web elements, increasingly necessary to achieve comprehensive, effective online communication, for instance blogs, microblogging platforms or social networks. The authors apply a methodology based on indicators from the Web Quality Index (WQI): a specific website analysis model for the tourism industry. The methodology provides a useful tool for examining and assessing how destination marketing organisations endow their websites with interactivity and connect them to the social media arena. The results show significant shortcomings in the websites for the aspects analysed, especially with regard to indicators linked to interactivity. Furthermore, the study suggests a series of measures that destination marketing organisations could adopt in order to remedy these shortcomings and optimise the relational aspects of their websites